DEVELOPER'S CAREER MASTERPLAN build your path to senior level and beyond with practical insights from industry experts - Vancura, Heather; Souza, Bruno (Packt Publishing Ltd., 2023)
Written by industry experts that have spent the last 20+ years helping developers grow their careers, this book offers invaluable insights and guidance tailored to the specific needs of technical professionals. By discovering the secret of continuous learning and adapting in the ever-evolving field of software development, you’ll explore various learning paths with formal and informal methods, as well as gain an understanding of the value of certifications to validate your skills. This book will teach you the significance of building a strong support network, holding crucial conversations, and taking ownership of your career growth. You'll delve into acquiring both soft and hard skills, becoming a well-rounded and sought-after developer. Packed with practical examples, stories of successful developers, and real-world applications, the chapters will equip you with actionable advice on how to push beyond your comfort zone and embracing communities to enhance your teamwork abilities. Additionally, you’ll uncover the benefits of joining open-source projects, speaking at conferences, and building a personal brand to amplify your visibility and reputation. By the end of this book, you'll have a well-laid-out long-term and short-term plan for your career progression, equipping you with advanced technical skills, strategic thinking, and the ability to effectively manage relationships within your organization.